Identification, classification and selection of warm mix additives based on workability, chemical and performance characteristics - Wagh V.P.; Gupta A.; Bhasin A. (My University, 2025)
Warm Mix Asphalt (WMA) technology enhances pavement sustainability by reducing energy consumption and emissions during the production of asphalt mixture. This study aimed to identify, classify and select suitable WMA additives based on the performance requirements for specific locations. Two base binders (VG30 and PMB40) and eight WMA additives were evaluated. Initially, the identification of WMA additives was carried out using workability approach by studying their reduction in mixing and compaction temperature. It was found that the workability approach was able to quantify the mixing and compaction temperatures for WMA modified binders. About 20°C and 17–22°C reduction in mixing and compaction temperatures, respectively, were obtained with the addition of different WMA additives. Fourier transform infrared spectroscopy (FTIR) has been employed for more precise classification of WMA additives based on functional groups. FTIR classified chemical additives into Amine–Silane and Amine-based additives whereas organic additives were classified as wax-type and Amine-based organic additives. The engineering relevance was demonstrated through performance evaluation of critical distresses such as rutting, fatigue cracking, low temperature cracking and moisture damage. A ranking framework was developed to guide the selection of WMA additives offering a systematic and practical tool for constructing durable asphalt pavements under diverse environmental and traffic conditions. © 2025 Informa UK Limited, trading as Taylor & Francis Group.